تنمية أداء الأستاذ الجامعي لخدمة المجتمع دراسة نظرية تفسيرية في المهام و المسؤوليات - دوباخ, قويدر (جامعة الوادي - University of Eloued, 2021)
يعتبر الأستاذ الجامعي المحور الأساسي في كل العملية التعليمية والتربوية، ولذلك تعمل جميع الأدبيات الأكاديمية في العالم على دراسته والاهتمام بكل ما يتعلق ببرامج تكوينه وتقويمه وتحديد طبيعة مهامه ومسؤولياته، وعلى الرغم من الانتشار الواسع لبرامج الرقمنة التي يشهدها العالم، التي تكاد تقزم من مكانة الأستاذ الجامعي، إلا أنّ مكانته رغم كل هذه الثورة الالكترونية في التعليم، لم تتزعزع وفي الحقيقة لن تتزعزع أبدا، فالأستاذ الجامعي دائما يعمل على التكيف وفق التطورات الحاصلة على جميع المستويات والأصعدة؛ ففي حقيقة الأمر لا يمكن بأي حال من الأحوال الحكم على قوة المؤسسات الجامعية دون التركيز على فكرة وجود طاقم بشري يقوده الأستاذ الجامعي الذي يعمل على أداء مجموعة من المهام والمسؤوليات المقدسة، التي لا تعتبر في حد ذاتها عبارة عن معايير عالمية لقياس مدى قوة المؤسسات الجامعية من عدمه، وبما أنّ الأستاذ الجامعي هو قيمة ومعطى نفسي ومتغير سلوكي بالدرجة الأولى، فإنه لابد من أن تتوفر فيه مجموعة من الخصائص المهنية والانفعالية والاجتماعية ليكون في مستوى التطلعات العالمية، التي تجعله قائدا لقاطرة التطور في العالم. الكلمات المفتاحية : التنمية ؛الأداء؛لأستاذ الجامعي ؛ خدمة المجتمع. Abstract: The university professor is considered the primary axis in the whole educational process and Training programs, and therefore all academic scholars in the world works to study him, and pay attention to everything related to its training and evaluation programs for determine the nature of his tasks and responsibilities, and despite the widespread of digitization programs and all this electronic revolution in education that the world is witnessing, but the position of the university professor has not wavered and in fact will never be shaken, because the university professor always works to adapt and taking the important place at all levels. In fact, it is not possible in any way to judge the strength of university institutions without focusing on the main idea of a human staff led by the university professor who works to perform a set of sacred tasks and responsibilities, which are not in themselves a global standard for measuring the strength of university institutions. The great values of the university professor are in many fields psychological, behavioral variable in the first place, also it’s an obligation that he must have a set of characteristics, professional, emotional and social to be at the level of global aspirations, which makes him a leader of the locomotive of development in the world.
developing the performance of the university professor for community service explanatory theory study of tasks and responsibilities
مقال
Keywords: التنمية ؛الأداء؛لأستاذ الجامعي ؛ خدمة المجتمع; Developing, performance , University professor, community service.